2012
DOI: 10.1590/s0365-05962012000300005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isotretinoin on triglycerides and liver aminotransferases

Abstract: BACKGROUND:Isotretinoin has been used to treat the most severe cases of acne; however, it may provoke adverse events in mucocutaneous and hepatic tissues, lead to alterations in lipid levels and cause teratogenicity. OBJECTIVE: The objective of this study was to evaluate the profile of changes in alanine aminotransferase (ALT), aspartate aminotransferase (AST) and triglyceride levels in patients who had been treated with oral isotretinoin dispensed by the São Mateus/ES pharmacy for special drugs. METHODS: A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 21 publications
6
32
0
4
Order By: Relevance
“…Laboratory tests for serum cholesterol and triglycerides as well as for AST and ALT indicates that all these tests show statistically significant rise in most patients included in the study, with more prominent increase in serum triglycerides (see Table 3). This agrees with previous studies that had shown increased values of serum cholesterol, triglycerides, AST, and ALT during treatment with oral isotretinoin with more prominent increase in serum triglycerides (8,13,15). However, when compared with the CTCAE (Table 1), our patients' laboratory values during treatment were still within normal ranges in most patients.…”
Section: Discussionsupporting
confidence: 92%
“…Laboratory tests for serum cholesterol and triglycerides as well as for AST and ALT indicates that all these tests show statistically significant rise in most patients included in the study, with more prominent increase in serum triglycerides (see Table 3). This agrees with previous studies that had shown increased values of serum cholesterol, triglycerides, AST, and ALT during treatment with oral isotretinoin with more prominent increase in serum triglycerides (8,13,15). However, when compared with the CTCAE (Table 1), our patients' laboratory values during treatment were still within normal ranges in most patients.…”
Section: Discussionsupporting
confidence: 92%
“…The most common side effects are mucocutaneous (dryness, keilit, palmoplantar exfoliation, rash, and dermatitis), gastrointestinal (inflammatory bowel disease), and ocular problems (conjunctivitis, dry eye) [4]. Besides these side effects, isotretinoin is known to cause several laboratory disturbances [8]. Severe hematological changes were previously reported as case reports [911].…”
Section: Introductionmentioning
confidence: 99%
“…Од-нако, по мнению некоторых авторов [56,63], оно может быть ассоциировано с повышением риска бо-лезней печени и сердечно-сосудистой системы. Именно поэтому рекомендуется исследовать сыво-роточный уровень ферментов до начала лечения, через 1 мес, а затем каждые 3 мес.…”
Section: клиническая дерматология и венерология 6 2015unclassified
“…Факторами риска считают макрокомедоны и круп-ные узлы. В более ранних работах [63] эксперты ре-комендовали для купирования обострения исполь-зовать короткие курсы (3-6 нед) приема преднизо-лона в суточной дозе 0,5-1,0 мг/кг. В настоящее время основной рекомендацией является повыше-ние суточной дозы изотретиноина до 1,0 мг/кг.…”
Section: клиническая дерматология и венерология 6 2015unclassified